How students’ entry-level competencies determine the learning needs of BIPA lectures? - Yuni Pratiwi; Imam Suyitno; Ary Fawzi; Dewi Ariani; Heni Dwi Arista; Ariva Luciandika (LPMPP Universitas Negeri Yogyakarta, 2022)
BIPA (the acronym of Bahasa Indonesia untuk Pelajar Asing) is one of the Indonesian-language learning programs for foreign learners. Understanding entry-level of student competencies are very useful as a starting point for preparing learning according to their learning needs in future lectures. This study aimed to describe how to assess student competence before conducting the lecture to determine their learning needs. This study used a qualitative and quantitative approach conducted in BIPA lectures involving seven lecturers as informants and 159 students as samples. Data were collected through document analysis, interviews, and tests. Qualitative data were used to describe the essential learning materials studied in BIPA lectures. Quantitative data were analyzed using the statistical tool 'Pearson Product Moment to assess entry-level competencies of students before taking courses. The results showed that the entry-level of students were in a low category. The correlation showed that the Grade Point Index (GPI) achieved in the previous lecture did not contribute significantly to student understanding in BIPA lectures because of the different substantial topic of the subjects. The low entry-level test scores reflect the students have not mastered the essential materials for BIPA lectures so they need to study them seriously. These findings can be used as a reference in determining the learning needs of students in the BIPA special program lectures. Therefore, these findings are useful for designing learning and determining policies that can meet the learning needs of students.